Representaciones sociales construidas sobre el cuerpo femenino por mujeres adolescentes, víctimas de explotación sexual (2018)
ABSTRACT: The objective of this study was to explore and review the social representations and the cognitive affective meanings that adolescent women victims have constructed on the female body. The reflection focused on "that" what is under that body's skin, that body constituted in an object of desire for who exploits it or who act as an intermediary; this study asked about social representations that different actors involved in this violation of rights have regarding victims' bodies, as well as, frank critiques regarding social and state convenience. Accordingly, the article proposes matters that contest some expert and institutional conceptualizations as social category. It was used to try to explain the type of relation established between an exploiter and an adolescent. This text is the result of an interaction of more than 2 years working with sexual exploitation victims, observing and recording in a field diary this issue in different contexts. This allowed the proposal of the two points of view presented herein. In an experiential workshop for adolescent women victims, constructions were obtained, and they enabled us to understand that which we could call a confiscated body. The poor social representation is basically that it is "a thing" for another person's enjoyment, without any interest in that person’s rights or in the damage that is caused. The type of violence that sexual exploitation victims suffer has been discharged systemically on their bodies; this justifies the pertinence of this discussion.